Methods of extraction, separation and identification of cyclic peptides from flaxseed (Linum usitatissimum L.): A review - R. V. Sobolev; I. E. Sokolov; N. A. Petrov; V. А. Sarkisyan; A. A. Kochetkova (Пищевые системы)
Oilseed flax (Linum usitatissimum L.) is a valuable crop characterized by a high content of fats, dietary fiber, protein and various biologically active substances, in particular cyclopeptides. Cyclic peptides are a group of cyclic hydrophobic peptides consisting of eight to ten amino acids with a molecular weight in the range of 950–2300 Da. Flax oil and seeds contain from 0.1 to 0.3% cyclopeptides, which can exhibit antioxidant, anti-inflammatory, immunosuppressive, antihypertensive and antitumor activity. The aim of this review was to systematize and summarize the available literature data on methods of extraction, separation and identification of cyclopeptides from flaxseed oil. It was found that the main methods for obtaining cyclopeptides are solid-liquid, liquid-liquid or solid-phase extraction. Commonly used solvents include methanol, hexane, ethyl acetate, dichloromethane, acetonitrile and deionized water. Preparative flash chromatography on silica gel or polymer adsorbents is used to purify and concentrate cyclopeptides, and high-performance liquid chromatography (HPLC) is used to obtain individual standards. The most commonly used stationary phases are non-polar modified sorbents — octadecyl (C18) and phenylhexyl functional groups. Identification is carried out using instrumental methods of analysis: IR spectroscopy, NMR, HPLC with a diode array detector (HPLC-PDA/DAD), high-resolution tandem mass spectrometry with electrospray ionization (ESI-HR-MS/MS). For the qualitative and quantitative determination of cyclopeptides, the HPLC with a diode array detector at a wavelength of 214 nm is sufficient. In turn, mass spectral methods, including tandem mass spectrometry, make it possible to confirm the qualitative composition and establish the amino acid sequence of cyclic peptides.